IoT-Based Dual Axis Solar Tracker Design on Monocrystalline Photovoltaic for Hydroponic Plant Water Pump Power Supply - Danarparasaji, Andrizal Haryufathanan; Haryudo, Subuh Isnur; Wrahatnolo, Tri; Rohman, Miftahur (Journal of Telecommunication Electronics and Control Engineering (JTECE), 2025)
Hydroponic growing media requires a continuous flow of water usually powered by PLN electricity. If the electricity supply is interrupted, the supply of plant nutrients will be disrupted. The utilization of renewable energy, such as photovoltaic, is an alternative solution. The efficiency of energy conversion is highly dependent on the placement of photovoltaic towards the position of the sun. Solar trackers that direct solar panels to follow the movement of the sun can increase the efficiency of photovoltaic. This research compares the performance of solar panel systems with and without solar trackers and tests the working duration of batteries for hydroponic water pump power supply. The Internet of Things (IoT) concept encompasses the idea of expanding the network of internet-connected devices to control and monitor devices remotely. The results show that the panel with the tracker produces an average voltage of 13.87 Volts and a current of 0.85 Amperes higher than without the tracker (13.36 Volts and 0.63 Amperes), with an efficiency of about 2% between the solar panel using the tracker and the one not using the tracker system. In addition, the battery can work for 12 hours to power the hydroponic water pump without the power obtained by the solar panel. For further development, it is recommended to use more advanced Internet of Things (IoT) technology and improved methods to increase the efficiency of the tracker system